2015
DOI: 10.1037/xlm0000107
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and nonverbal cognitive control in bilinguals and interpreters.

Abstract: The present study explored the relation between language control and nonverbal cognitive control in different bilingual populations. We compared monolinguals, Dutch-French unbalanced bilinguals, balanced bilinguals, and interpreters on the Simon task (Simon & Rudell, 1967) and the Attention Network Test (ANT; Fan, McCandliss, Sommer, Raz, & Posner, 2002). All bilingual groups showed a smaller congruency effect in the Simon task than the monolingual group. They were also faster overall in the ANT. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
92
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 43 publications
10
92
2
2
Order By: Relevance
“…Some studies have examined effects of bilingualism in a non-immigrant sample and have found positive effects for healthy adults (e.g., Bak, Nissan, Allerhand, & Deary, 2014;Costa et al, 2008;Woumans, Ceuleers, Van der Linden, Szmalec, & Duyck, 2015) and dementia patients (Alladi et al, 2013;Woumans, Santens et al, 2015). On the other hand, studies with non-immigrant samples did not observe a cognitive effect of bilingualism in children (e.g., Antón et al, 2014), younger adults (e.g., Kousaie & Phillips, 2012a, although some differences were found in the ERP data), healthy older adults (e.g., Kousaie & Phillips, 2012b), and dementia patients (e.g., Chertkow et al, 2010;Lawton, Gasquoine, & Weimer, 2015).…”
Section: The Importance Of Confounding Variablesmentioning
confidence: 98%
“…Some studies have examined effects of bilingualism in a non-immigrant sample and have found positive effects for healthy adults (e.g., Bak, Nissan, Allerhand, & Deary, 2014;Costa et al, 2008;Woumans, Ceuleers, Van der Linden, Szmalec, & Duyck, 2015) and dementia patients (Alladi et al, 2013;Woumans, Santens et al, 2015). On the other hand, studies with non-immigrant samples did not observe a cognitive effect of bilingualism in children (e.g., Antón et al, 2014), younger adults (e.g., Kousaie & Phillips, 2012a, although some differences were found in the ERP data), healthy older adults (e.g., Kousaie & Phillips, 2012b), and dementia patients (e.g., Chertkow et al, 2010;Lawton, Gasquoine, & Weimer, 2015).…”
Section: The Importance Of Confounding Variablesmentioning
confidence: 98%
“…A few studies found that bilingualism did not bring WM advantage as measured by WM spans (e.g., Ratiu and Azuma, 2015). Bilingual advantage in monitoring (as indicated by shortened reaction times in tasks containing conflicts or by mixing cost in the color-shape task) was reported too (e.g., Barac and Bialystok, 2012; Abutalebi et al, 2015; Woumans et al, 2015). However, null bilingual effects have also been reported in the Simon task (e.g., Gathercole et al, 2014; Kirk et al, 2014), the Stroop task (e.g., Kousaie and Phillips, 2012) and the flanker task (e.g., Bialystok et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition advantage from bilingualism was evidenced in different tasks, such as the Simon task (e.g., Bialystok et al, 2004; Carlson and Meltzoff, 2008; Woumans et al, 2015), the Stroop task (e.g., Bialystok et al, 2008; Blumenfeld and Marian, 2011), the flanker task (e.g., de Abreu et al, 2012; Poarch and Bialystok, 2015) and the Attention Network Test (ANT; a complex version of flanker) (e.g., Costa et al, 2008; Marzecová et al, 2013). Bilingual advantage in switching was shown in the color-shape task (e.g., Prior and Macwhinney, 2010; Prior and Gollan, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong and Xie (2014) compared students of interpretation to students of other subjects on the flanker task and found no difference in performance. Similarly, Woumans and colleagues found no differences between students of interpretation and balanced bilinguals on the Attention Network Test (ANT) and Simon task (Woumans et al 2015).…”
Section: Introductionmentioning
confidence: 99%